A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom and preparation method thereof

By adopting the heterogeneous structure of the platinum single atom in the photocatalyst and the cobalt cage complexion of the vulcoria and the hollow, the cobalt cobalt oxides, the photocopy of the cage in the cage of the platinum single atom is to solve the problem of loss and carrier consumption in the seawater, and realize it. Efficient photocatalytic decomposition and stability improvement.

CN118558334BActive Publication Date: 2025-01-28YAOLING TIMES (SHANDONG) NEW ENERGY TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410638822.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-01-28
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

Existing photocatalysts are prone to inactivation when used in natural seawater, and the adverse consumption of photogenerated carriers hinders practical application.

Method used

The vulcanized zinc cymbal and hollow duodenal cobalt oxide intra cage complex anchor the heterogeneous structure of the platinum single atom, which is used to achieve the efficient space separation of photocopy electronic cavities through the hollow nuclear shell covering structure, and uses surface sulfur The empty level is anchoring the platinum single atom as the active site to regulate the electronic structure of zinc sulfide.

Benefits of technology

It significantly improves the activity and stability of the hydrogenation of sea water and pure water, improves the activity of appearance and internal photocatalytic, and enhances the corrosion resistance of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118558334B_ABST
    Figure CN118558334B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of photocatalytic solar energy conversion, and specifically to a heterostructure photocatalyst of zinc indium sulfide and hollow dodecahedral cobalt oxide inner cage complex anchoring platinum single atom and a preparation method thereof. The photocatalyst is a sulfur vacancy-rich ZnIn2S4 nanosheet chemically anchored in a hollow dodecahedral CoO by a hydrothermal method. X The outer surface of the nanocage, and then the obtained CoO X The ZnIn2S4 complex was subjected to dark chemical reduction to deposit Pt single atoms to form a hierarchical heterostructure. The Pt single atoms were anchored in the S vacancies as the active sites for the reduction reaction on the outer surface, while the photogenerated holes were captured by the internal CoOx cages and participated in the Co 2+ / Co 3+ The spatially separated redox centers are expected to mediate the efficient bidirectional separation of photogenerated electrons and holes, thereby avoiding the rapid recombination annihilation of photogenerated carriers. X @ZnIn2S4‑Pt SA heterostructure photocatalyst can be used as a photocatalyst to significantly improve the activity and stability of photocatalytic decomposition of seawater and hydrogen evolution in pure water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photocatalytic solar energy conversion, and specifically relates to a heterostructure photocatalyst of a zinc indium sulfide and a hollow regular dodecahedral cobalt oxide inner cage complex anchoring a platinum single atom and a preparation method thereof. Background Art

[0002] Using semiconductor photocatalytic technology to produce hydrogen from abundant natural seawater resources is a technically feasible and promising approach that is expected to help overcome the energy crisis and accelerate the pace of carbon neutrality.

[0003] However, due to the complex ionic environment and side reactions in seawater, the deactivation of photocatalysts and the unfavorable consumption of photogenerated carriers hinder practical applications. Therefore, when designing efficient photocatalysts for natural seawater splitting, corrosion resistance and inhibition of side reactions should be given priority. In addition, the separation and transfer of photogenerated charges and the kinetics of surface redox reactions compete fiercely with the charge recombination deactivation process. Modifying dual co-catalysts on semiconductor photocatalysts is one of the effective approaches. It not only provides power for the directional separation and anisotropic migration of photogenerated electrons and holes, but also provides additional active sites for surface catalytic reactions and reduces the reaction energy barrier. Typically, noble metals such as Pt, Rh, and Au are usually modified as electron sinks to effectively reduce protons to hydrogen, while metal oxides such as CoO x MnO x 、RuO 2 、IrO 2 ) is usually used as an oxidation co-catalyst. For reduction co-catalysts, Pt has a higher work function and partially unoccupied 5d orbitals, which are conducive to adsorbing electrons and improving hydrogen evolution activity. However, minimizing the loading of precious metals and maximizing the atomic utilization efficiency while maintaining or even improving the catalytic performance remains a difficult task.

[0004] In addition, in the photocatalytic system with randomly distributed dual co-catalysts, since the flow direction of carriers is arbitrary, the electronic co-catalyst may be deposited in the hole-rich region, which is prone to charge carrier recombination and is not conducive to the occurrence of surface reactions. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a heterostructure photocatalyst of zinc indium sulfide and hollow dodecahedral cobalt oxide inner cage complex anchoring platinum single atoms and a preparation method thereof. Through the hollow core-shell coating structure, a three-dimensional isolated distribution of reduction and oxidation co-catalysts is constructed, thereby achieving efficient spatial separation of photogenerated electron holes; using surface sulfur vacancies to anchor platinum single atoms as active sites provides additional degrees of freedom for adjusting the electronic structure of zinc indium sulfide, thereby helping to achieve higher apparent and intrinsic photocatalytic activity. Photogenerated holes participate in the oxidation of Co in the cobalt oxide cage. 2+ / Co 3+ The material exhibits excellent photocatalytic activity and corrosion resistance in the universal hydrogen evolution of natural seawater and pure water after dynamic reconstruction.

[0006] In order to achieve the above invention object, the technical solution of the present invention is as follows:

[0007] The invention discloses a heterostructure photocatalyst in which a single platinum atom is anchored by a complex of zinc indium sulfide (rich in sulfur vacancies) and a hollow dodecahedral cobalt oxide inner cage. The photocatalyst is a hierarchical heterostructure photocatalyst in which a two-dimensional zinc indium sulfide nanosheet rich in sulfur vacancies is chemically coated on the outside of a hollow dodecahedral cobalt oxide cage by a hydrothermal method to construct a heterostructure composite, and a single Pt atom is chemically reduced and anchored by sulfur vacancies on the surface of the composite.

[0008] Furthermore, the mass ratio of the cobalt oxide to zinc indium sulfide is 0.1 to 3.0%; the mass ratio of the platinum single atom to the composite of zinc indium sulfide coated cobalt oxide is 0.1 to 1.0%.

[0009] The present invention also discloses a preparation method of a heterostructure photocatalyst of a zinc indium sulfide and a hollow regular dodecahedral cobalt oxide inner cage complex anchoring a platinum single atom, comprising the following steps:

[0010] S1, a step of preparing cobalt oxide by heat treatment in air atmosphere;

[0011] S2, a step of preparing a zinc indium sulfide reaction precursor solution rich in sulfur vacancies, and chemically anchoring the zinc indium sulfide nanosheets rich in sulfur vacancies on the outer surface of the hollow dodecahedral cobalt oxide hollow cage by a hydrothermal method to construct a cobalt oxide@zinc indium sulfide heterostructure composite;

[0012] S3, a step of preparing a reaction precursor solution containing Pt, and using a dark chemical reduction method to anchor platinum single atoms on sulfur vacancies on the surface of the cobalt oxide@zinc indium sulfide complex to construct a cobalt oxide@zinc indium sulfide-platinum single-atom-level heterostructure photocatalyst.

[0013] Further, in step S1, the preparation of cobalt oxide comprises the following steps:

[0014] a. Dissolve dimethylimidazole and cobalt nitrate hexahydrate in methanol solution respectively. Pour the uniformly mixed dimethylimidazole methanol solution into the cobalt nitrate hexahydrate methanol solution quickly. Stir the obtained purple solution vigorously and let it stand at room temperature for aging. Collect the obtained purple precipitate by high-speed centrifugation, then wash with ethanol and dry under vacuum at room temperature to obtain a zeolite imidazole ester cobalt metal framework material (ZIF-67).

[0015] b. Grind the dried ZIF-67 powder and place it in a covered porcelain boat, and place the porcelain boat in a quartz tube of a tubular furnace for heat treatment under air atmosphere; obtain a cobalt oxide material.

[0016] Furthermore, in step a, the mass ratio of dimethylimidazole to cobalt nitrate hexahydrate is 0.5-2.0; and the volume of the methanol solution is 50 mL-150 mL.

[0017] Further, in step b, the temperature is raised to 300-400°C at a heating rate of 1-5°C / min, and the temperature is kept constant for 1min-60min, and then naturally cooled to room temperature. The cobalt oxide CoO X The value of X is 1.0-2.0.

[0018] Further, step S2 includes the following steps:

[0019] a. Add cobalt oxide to ethanol, ethylene glycol, glycerol or deionized water and disperse evenly to obtain a cobalt oxide solution;

[0020] b. adding the zinc source and the indium source to the above solution a and dispersing them uniformly to obtain a reaction precursor solution containing no sulfur source, stirring and dispersing them uniformly, and finally adding the sulfur source and dispersing them uniformly to obtain a reaction precursor solution;

[0021] c. placing the reaction precursor solution in a high temperature reactor for high temperature reaction to obtain a cobalt oxide@zinc indium sulfide heterostructure composite.

[0022] Furthermore, in step b, the zinc source is one of zinc chloride, zinc acetate, zinc sulfate, and zinc nitrate; the indium source is indium chloride; and the sulfur source is one of thiourea, thioacetamide, sodium sulfide, and sulfur powder.

[0023] Furthermore, in step b, the atomic ratio of the sulfur source to the zinc source in the precursor solution is S / Zn=4-12.

[0024] Further, step S3 includes the following steps:

[0025] a. uniformly dissolving the obtained cobalt oxide@zinc indium sulfide heterostructure complex in a methanol solution;

[0026] b. Disperse chloroplatinic acid hexahydrate evenly in a methanol solution, and add dropwise to the cobalt oxide @ zinc indium sulfide methanol solution in a, and introduce argon gas to remove impurities, and stir slowly for 48 hours in the dark. Collect the obtained sample by centrifugation, wash it with ethanol several times, and dry it at room temperature in a nitrogen flow for 8 hours.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (I) The heterostructure photocatalyst of zinc indium sulfide and hollow dodecahedral cobalt oxide inner cage complex anchoring platinum single atom and its preparation method disclosed in the present invention is to convert sulfur vacancy-rich ZnIn 2 S 4 The nanosheets were chemically anchored on the hollow dodecahedron CoO via a hydrothermal method. X The outer surface of the nanocage, and then the obtained CoO X @ZnIn 2 S 4 The complex undergoes dark chemical reduction to deposit Pt single atoms to form a hierarchical heterostructure. Pt single atoms are anchored in S vacancies as active sites for the reduction reaction on the outer surface, while the photogenerated holes are driven by the internal CoO x Cage capture and participation in Co 2+ / Co 3+ The spatially separated redox centers are expected to mediate the efficient bidirectional separation of photogenerated electrons and holes, thereby avoiding the rapid recombination annihilation of photogenerated carriers.

[0029] (II) CoO prepared by the method of the present invention X @ZnIn 2 S 4 -Pt SA heterostructure photocatalyst, benefiting from the design of spatially separated carrier separation pathways and Co 2+ / Co 3+ In-situ self-reconstruction behavior can be used as a photocatalyst to significantly improve the activity and stability of photocatalytic decomposition of seawater and hydrogen evolution from pure water. The present invention designs a hollow core-shell coating structure to construct a three-dimensional isolated distribution of reduction and oxidation co-catalysts, thereby achieving efficient spatial separation of photogenerated electron holes; using surface sulfur vacancies to anchor platinum single atoms as active sites provides additional degrees of freedom for adjusting the electronic structure of zinc indium sulfide, thereby helping to achieve higher apparent and intrinsic photocatalytic activity. Photogenerated holes participate in the CoO2 cage 2+ / Co 3+ The dynamic reconstruction greatly improves photocorrosion and enhances the catalytic stability of the material. The above lays a solid foundation for the high photocatalytic activity and corrosion resistance of the material in the universal hydrogen evolution of natural seawater and pure water by photocatalytic cracking. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 CoO prepared in Example 1 of the present invention X SEM image of @ZIS-Pt SA.

[0031] Figure 2 CoO prepared in Example 1 of the present invention X X-ray diffraction spectrum of @ZIS-Pt SA.

[0032] Figure 3This is a column comparison chart of the photocatalytic pure water hydrogen decomposition rate of the materials prepared in Example 1 of the present invention.

[0033] Figure 4 (a, c) curves of hydrogen evolution rate versus time for photocatalytic decomposition of seawater and pure water by the material prepared in Example 1 of the present invention, and (b, d) columnar comparison charts of photocatalytic hydrogen evolution rate.

[0034] Figure 5 (a) Photocurrent spectrum and (b) electrochemical impedance spectrum of the material prepared in Example 1 of the present invention.

[0035] Figure 6 This is a diagram of the photocatalytic mechanism of the material prepared in the embodiment of the present invention.

[0036] Figure 7 This is a bar chart comparing the photocatalytic (a) pure water decomposition and (b) seawater decomposition and hydrogen decomposition rates of the materials prepared in Comparative Examples 3 to 5 of the present invention. DETAILED DESCRIPTION

[0037] A heterostructure photocatalyst of zinc indium sulfide and hollow dodecahedral cobalt oxide inner cage complex anchoring platinum single atoms, the photocatalyst will be rich in sulfur vacancies ZnIn 2 S 4 The nanosheets were chemically anchored on the hollow dodecahedron CoO via a hydrothermal method. X The outer surface of the nanocage, and then the obtained CoO X @ZnIn 2 S 4 The complex is subjected to dark chemical reduction to deposit Pt single atoms to form a hierarchical heterogeneous structure photocatalyst. The present invention modifies a dual promoter on a semiconductor photocatalyst, which not only provides power for the directional separation and anisotropic migration of photogenerated electrons and holes, but also provides additional active sites for surface catalytic reactions and reduces the reaction energy barrier.

[0038] In summary, the heterostructure composite material of zinc indium sulfide and hollow dodecahedral cobalt oxide inner cage complex anchoring platinum single atoms utilizes platinum single atoms and CoO X The sulfur vacancies on the surface of the ZIS heterojunction anchor single Pt atoms on the S vacancies of the ZIS nanosheets, inducing charge redistribution at the interface. The Pt single atoms are anchored on the S vacancies as active sites for the reduction reaction on the outer surface, while the photogenerated holes are captured by the internal CoOx cages and participate in the Co 2+ / Co 3+ The spatially separated redox centers achieve efficient bidirectional separation of photogenerated electrons and holes, thereby effectively avoiding the rapid recombination annihilation of photogenerated carriers, and thus significantly improving the photocatalytic activity and stability.

[0039] The mass ratio of the cobalt oxide to the zinc indium sulfide is 0.1 to 3.0%, and the most preferred mass ratio of the cobalt oxide to the zinc indium sulfide is 2.0%. ZnIn rich in sulfur vacancies 2 S 4 The product preferably has S / Zn=6.0. The mass ratio of the complex of the single platinum atom and the zinc indium sulfide coated cobalt oxide is 0.1-1.0%; the most preferably mass ratio of the complex of the single platinum atom and the zinc indium sulfide coated cobalt oxide is 0.75%.

[0040] A method for preparing a heterostructure photocatalyst in which a complex formed by zinc indium sulfide rich in sulfur vacancies and a hollow regular dodecahedral cobalt oxide inner cage anchors a single platinum atom, characterized in that it comprises the following steps:

[0041] S1, a step of preparing cobalt oxide by heat treatment in air atmosphere;

[0042] S2, the step of preparing a sulfur vacancy-rich zinc indium sulfide reaction precursor solution, and chemically anchoring the sulfur vacancy-rich zinc indium sulfide nanosheets on the outer surface of the hollow dodecahedral cobalt oxide hollow cage by a hydrothermal method to construct a cobalt oxide@zinc indium sulfide heterostructure composite.

[0043] S3, a step of preparing a reaction precursor solution containing Pt, and using a dark chemical reduction method to anchor platinum single atoms on sulfur vacancies on the surface of the cobalt oxide@zinc indium sulfide complex to construct a cobalt oxide@zinc indium sulfide-platinum single-atom-level heterostructure photocatalyst.

[0044] In step S1, the preparation of cobalt oxide comprises the following steps:

[0045] a. Dissolve dimethylimidazole and cobalt nitrate hexahydrate in methanol solution respectively. Pour the evenly mixed dimethylimidazole methanol solution into the cobalt nitrate hexahydrate methanol solution quickly. The mass ratio of dimethylimidazole to cobalt nitrate hexahydrate is 0.5-2.0, and the optimal mass ratio is 1:1. The volume of the methanol solution is 50mL-150mL, and the optimal volume is 100mL. The obtained purple solution is vigorously stirred and allowed to stand at room temperature for 24 hours. The obtained purple precipitate is collected by high-speed centrifugation, then washed with ethanol and dried in vacuum at room temperature to obtain a zeolite imidazole ester cobalt metal framework material (ZIF-67); the mass ratio of dimethylimidazole to cobalt nitrate hexahydrate determines the size of the obtained ZIF-67, and the appropriate hollow cage size will be easier to form a good geometric coating with zinc indium sulfide.

[0046] b. Grind the dried ZIF-67 powder and place it in a covered porcelain boat, and place the porcelain boat in a tubular furnace quartz tube for heat treatment in air atmosphere to obtain cobalt oxide material. The tubular furnace is heated to 300-400℃ at a heating rate of 1-5℃ / min, and the temperature is kept constant for 1min-60min, and then naturally cooled to room temperature. The best preferred heating condition is to heat to 400℃ at 1℃ / min and keep the temperature constant for 1min. The heating conditions, as well as the insulation temperature and time, affect the oxidation degree and topological morphology integrity of the obtained cobalt oxide.

[0047] Step S2 includes the following steps:

[0048] a. Add cobalt oxide to ethanol, ethylene glycol, glycerol or deionized water and disperse evenly to obtain a cobalt oxide solution;

[0049] b. Add the zinc source and indium source to the above solution a and disperse them evenly to obtain a reaction precursor solution without a sulfur source. After fully stirring and dispersing them evenly, finally add the sulfur source and disperse them evenly to obtain a reaction precursor solution. The zinc source is one of zinc chloride, zinc acetate, zinc sulfate, and zinc nitrate; the indium source is indium chloride; the sulfur source is one of thiourea, thioacetamide, sodium sulfide, and sulfur powder. Appropriate input ratios of zinc, indium, and sulfur precursor sources are conducive to the preparation of ZnIn rich in vacancies and with complete two-dimensional flake distribution. 2 S 4 Reaction product; most preferably, the zinc source is zinc chloride, the indium source is indium chloride, and the sulfur source is thioacetamide.

[0050] c. placing the reaction precursor solution in a high temperature reactor for high temperature reaction to obtain a cobalt oxide@zinc indium sulfide heterostructure composite.

[0051] The mass ratio of the cobalt oxide to the zinc indium sulfide is 0.1 to 3.0, and the most preferred mass ratio of the cobalt oxide to the zinc indium sulfide is 2.0%. The zinc indium sulfide product rich in sulfur vacancies, the atomic ratio of the sulfur source to the zinc source in the precursor solution is S / Zn=4 to 12, and the most preferred is S / Zn=6.0.

[0052] Step S3 includes the following steps:

[0053] a. uniformly dissolving the obtained cobalt oxide@zinc indium sulfide heterostructure complex in a methanol solution;

[0054] b. Disperse chloroplatinic acid hexahydrate evenly in a methanol solution, and add dropwise to the cobalt oxide @ zinc indium sulfide methanol solution in a, and pass argon gas to remove impurities, and stir slowly for 48 hours in the dark and away from light. The obtained sample is collected by centrifugation, washed with ethanol several times, and dried at room temperature in a nitrogen flow for 8 hours. The mass ratio of the complex of platinum single atom and zinc indium sulfide coated cobalt oxide is 0.1-1.0%; preferably, the mass ratio of the complex of platinum single atom and zinc indium sulfide coated cobalt oxide is 0.75%, and the obtained catalyst has high photocatalytic hydrogen evolution activity.

[0055] Compared with the prior art, the catalyst prepared in the above embodiment has the following effects:

[0056] (1) The synthesized zinc indium sulfide and hollow dodecahedral cobalt oxide inner cage complex anchored platinum single atoms in the heterostructured photocatalyst, through the hollow core-shell coating structure, constructs a three-dimensional isolated distribution of reduction and oxidation co-catalysts, thereby achieving efficient spatial separation of photogenerated electrons and holes;

[0057] (2) The use of surface sulfur vacancies to anchor Pt single atoms as active sites provides additional degrees of freedom for tuning the electronic structure of ZnInS, thus helping to achieve higher apparent and intrinsic photocatalytic activities.

[0058] (3) Photogenerated holes participate in the Co 2+ / Co 3+ The dynamic reconstruction enables the material to exhibit excellent photocatalytic activity and corrosion resistance when used for universal hydrogen evolution in the photocatalytic cracking of natural seawater and pure water.

[0059] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0060] Any feature disclosed in this specification (including claims and abstract), unless otherwise stated, may be replaced by other equivalent or alternative features having similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0061] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0062] Embodiment 1:

[0063] A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom, the preparation method of which comprises the following steps:

[0064] The first step is the preparation of cobalt oxide:

[0065] a. 2.34 g of dimethyl imidazole and 2.34 g of cobalt nitrate hexahydrate were dissolved in 100 mL of methanol solution. The uniformly mixed dimethyl imidazole methanol solution was quickly poured into the cobalt nitrate hexahydrate methanol solution to obtain a purple solution. The obtained purple solution was vigorously stirred for 20 minutes and allowed to stand at room temperature for 24 hours. The obtained purple precipitate was collected at a high speed centrifugation rate of 8000 rpm, then washed 8 times with ethanol and dried under vacuum at room temperature to obtain a zeolite imidazole ester cobalt metal framework material (ZIF-67).

[0066] b. Grind the dried ZIF-67 to obtain ZIF-67 powder, then spread the ZIF-67 powder thinly in a covered porcelain boat, and place the porcelain boat in a tubular furnace quartz tube for heat treatment in air atmosphere to obtain cobalt oxide material. The tubular furnace is heated to 400°C at a heating rate of 1°C / min, and the temperature is kept constant for 1 minute, and then naturally cooled to room temperature. Take out the sample and store it in a vacuum.

[0067] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0068] a. A certain amount of the cobalt oxide prepared in the first step is uniformly dispersed in 50 mL of ethylene glycol and vigorously stirred for 10 minutes to obtain a cobalt oxide solution;

[0069] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0070] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0071] Step 3: Preparation of cobalt oxide@zinc indium sulfide-platinum single atomic level heterostructure composite materials:

[0072] a. The obtained 50 mg cobalt oxide @ zinc indium sulfide heterostructure complex was uniformly dispersed in 80 mL methanol solution by ultrasonic stirring;

[0073] b. The mass ratio of the complex of platinum single atom and zinc indium sulfide coated cobalt oxide is uniformly ultrasonically dispersed in 20 mL of methanol solution with chloroplatinic acid hexahydrate, and slowly added dropwise to the cobalt oxide @ zinc indium sulfide methanol solution described in a, and argon gas is introduced to remove impurities, and the mixture is slowly stirred for 48 hours in the dark. The obtained sample is collected by centrifugation, washed repeatedly with ethanol and water for 4 times, and dried at room temperature in a nitrogen gas flow for 8 hours to obtain a cobalt oxide @ zinc indium sulfide-platinum single atom-level heterogeneous structure composite material.

[0074] Embodiment 2:

[0075] A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom, the preparation method of which comprises the following steps:

[0076] The first step, preparation of cobalt oxide: the preparation method is the same as that in Example 1;

[0077] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0078] a. 2.117 g of cobalt oxide was uniformly dispersed in 50 mL of ethylene glycol and stirred vigorously for 10 minutes to obtain a cobalt oxide solution;

[0079] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0080] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0081] d. By attaching Figure 3 It can be seen that the CoO prepared in this example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X The photocatalytic hydrogen decomposition rate of pure water by @ZIS-0.5 is 6.57 mmol g -1 h -1 .

[0082] Embodiment 3:

[0083] A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom, the preparation method of which comprises the following steps:

[0084] The first step, preparation of cobalt oxide: the preparation method is the same as that in Example 1.

[0085] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0086] a. Disperse 4.233 g of cobalt oxide evenly in 50 mL of ethylene glycol and stir vigorously for 10 minutes to obtain a cobalt oxide solution;

[0087] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0088] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0089] d. By attaching Figure 3 It can be seen that the CoO prepared in this example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X The photocatalytic hydrogen decomposition rate of pure water by @ZIS-1.0 is 16.11 mmol g -1 h -1 .

[0090] Embodiment 4:

[0091] A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom, the preparation method of which comprises the following steps:

[0092] The first step, preparation of cobalt oxide: the preparation method is the same as that in Example 1.

[0093] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0094] a. 8.466 g of cobalt oxide was uniformly dispersed in 50 mL of ethylene glycol and stirred vigorously for 10 minutes to obtain a cobalt oxide solution;

[0095] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0096] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0097] d. By attaching Figure 3 4 It can be seen that the CoO prepared in this example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X The photocatalytic hydrogen decomposition rate of @ZIS-2.0 was 10.62 mmol g -1 h -1 The photocatalytic hydrogen release rate of pure water is 19.63 mmol g -1 h -1 .

[0098] Embodiment 5:

[0099] A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom, the preparation method of which comprises the following steps:

[0100] The first step is the preparation of cobalt oxide. The preparation method of cobalt oxide is the same as that of Example 1.

[0101] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0102] a. Disperse 21.165 g of cobalt oxide evenly in 50 mL of ethylene glycol and stir vigorously for 10 minutes to obtain a cobalt oxide solution;

[0103] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0104] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0105] d. By attaching Figure 3 It can be seen that the CoO prepared in this example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X The photocatalytic hydrogen decomposition rate of pure water by @ZIS-3.0 is 14.95mmol g -1 h -1.

[0106] Embodiment 6:

[0107] A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom, the preparation method of which comprises the following steps:

[0108] The first step, preparation of cobalt oxide: the preparation method is the same as that in Example 1;

[0109] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0110] a. 8.466 g of cobalt oxide was uniformly dispersed in 50 mL of ethylene glycol and stirred vigorously for 10 minutes to obtain a cobalt oxide solution;

[0111] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0112] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0113] Step 3: Preparation of cobalt oxide@zinc indium sulfide-platinum single atomic level heterostructure composite materials:

[0114] a. The obtained 50 mg cobalt oxide @ zinc indium sulfide heterostructure complex was uniformly dispersed in 80 mL methanol solution by ultrasonic stirring;

[0115] b. The mass ratio of the platinum single atom and the zinc indium sulfide-coated cobalt oxide composite is 0.25% chloroplatinic acid hexahydrate, which is uniformly ultrasonically dispersed in 20 mL of methanol solution, and slowly added dropwise to the cobalt oxide @ zinc indium sulfide methanol solution described in a, and argon gas is introduced to remove impurities, and the mixture is slowly stirred for 48 hours in the dark. The obtained sample is collected by centrifugation, washed repeatedly with ethanol and water for 4 times, and dried at room temperature in a nitrogen flow for 8 hours to obtain a cobalt oxide @ zinc indium sulfide-platinum single atom-level heterogeneous structure composite material.

[0116] c. By attaching Figure 3 It can be seen that the CoO prepared in this example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X The photocatalytic hydrogen release rate of pure water by @ZIS-Pt 0.25 is 25.83 mmol g-1 h -1 .

[0117] Embodiment 7:

[0118] A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom, the preparation method of which comprises the following steps:

[0119] The first step, preparation of cobalt oxide: the preparation method is the same as that in Example 1;

[0120] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0121] a. 8.466 g of cobalt oxide was uniformly dispersed in 50 mL of ethylene glycol and stirred vigorously for 10 minutes to obtain a cobalt oxide solution;

[0122] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0123] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0124] Step 3: Preparation of cobalt oxide@zinc indium sulfide-platinum single atomic level heterostructure composite materials:

[0125] a. The obtained 50 mg cobalt oxide @ zinc indium sulfide heterostructure complex was uniformly dispersed in 80 mL methanol solution by ultrasonic stirring;

[0126] b. The mass ratio of the platinum single atom and the zinc indium sulfide-coated cobalt oxide composite is 0.50% chloroplatinic acid hexahydrate, which is uniformly ultrasonically dispersed in 20 mL of methanol solution, and slowly added dropwise to the cobalt oxide @ zinc indium sulfide methanol solution described in a, and argon gas is introduced to remove impurities, and the mixture is slowly stirred for 48 hours in the dark. The obtained sample is collected by centrifugation, washed repeatedly with ethanol and water for 4 times, and dried at room temperature in a nitrogen gas flow for 8 hours to obtain a cobalt oxide @ zinc indium sulfide-platinum single atom-level heterogeneous structure composite material.

[0127] c. By attaching Figure 3 It can be seen that the CoO prepared in this example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. XThe photocatalytic hydrogen release rate of pure water by @ZIS-Pt 0.50 is 45.86 mmol g -1 h -1 .

[0128] Embodiment 8:

[0129] A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom, the preparation method of which comprises the following steps:

[0130] The first step, preparation of cobalt oxide: the preparation method is the same as that in Example 1;

[0131] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0132] a. 8.466 g of cobalt oxide was uniformly dispersed in 50 mL of ethylene glycol and stirred vigorously for 10 minutes to obtain a cobalt oxide solution;

[0133] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0134] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0135] Step 3: Preparation of cobalt oxide@zinc indium sulfide-platinum single atomic level heterostructure composite materials:

[0136] a. The obtained 50 mg cobalt oxide @ zinc indium sulfide heterostructure complex was uniformly dispersed in 80 mL methanol solution by ultrasonic stirring;

[0137] b. The mass ratio of the platinum single atom and the zinc indium sulfide-coated cobalt oxide composite is 0.75% chloroplatinic acid hexahydrate, which is uniformly ultrasonically dispersed in 20 mL of methanol solution, and slowly added dropwise to the cobalt oxide @ zinc indium sulfide methanol solution described in a, and argon gas is introduced to remove impurities, and the mixture is slowly stirred for 48 hours in the dark. The obtained sample is collected by centrifugation, washed repeatedly with ethanol and water for 4 times, and dried at room temperature in a nitrogen flow for 8 hours to obtain a cobalt oxide @ zinc indium sulfide-platinum single atom-level heterogeneous structure composite material.

[0138] c. By attaching Figure 34 It can be seen that the CoO prepared in this example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X @ZIS-Pt 0.75, the photocatalytic hydrogen decomposition rate of seawater is 23.74mmol g -1 h -1 The photocatalytic hydrogen release rate of pure water is 48.99 mmol g -1 h -1 .

[0139] Embodiment 9:

[0140] A heterostructure photocatalyst of zinc indium sulfide and hollow regular dodecahedral cobalt oxide inner cage complex anchoring platinum single atom, the preparation method of which comprises the following steps:

[0141] The first step, preparation of cobalt oxide: the preparation method is the same as that in Example 1;

[0142] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0143] a. 8.466 g of cobalt oxide was uniformly dispersed in 50 mL of ethylene glycol and stirred vigorously for 10 minutes to obtain a cobalt oxide solution;

[0144] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0145] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0146] Step 3: Preparation of cobalt oxide@zinc indium sulfide-platinum single atomic level heterostructure composite materials:

[0147] a. The obtained 50 mg cobalt oxide @ zinc indium sulfide heterostructure complex was uniformly dispersed in 80 mL methanol solution by ultrasonic stirring;

[0148] b. The mass ratio of the platinum single atom and the zinc indium sulfide-coated cobalt oxide composite is 1.0% chloroplatinic acid hexahydrate, which is uniformly ultrasonically dispersed in 20 mL of methanol solution, and slowly added dropwise to the cobalt oxide @ zinc indium sulfide methanol solution described in a, and argon gas is introduced to remove impurities, and the mixture is slowly stirred for 48 hours in the dark. The obtained sample is collected by centrifugation, and repeatedly washed with ethanol and water for 4 times, and dried at room temperature in a nitrogen flow for 8 hours to obtain a cobalt oxide @ zinc indium sulfide-platinum single atom-level heterogeneous structure composite material.

[0149] c. By attaching Figure 3 It can be seen that the CoO prepared in this example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X The photocatalytic hydrogen release rate of pure water by @ZIS-Pt 1.0 is 45.09 mmol g -1 h -1 .

[0150] Comparative Example 1:

[0151] The first step is the preparation of zinc indium sulfide nanosheet photocatalyst:

[0152] a. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to 50 mL of ethylene glycol solution and dispersed evenly to obtain a reaction precursor solution without a sulfur source. After stirring for 30 minutes to make it evenly dispersed, 450 mg of thioacetamide was finally added and dispersed evenly to obtain a reaction precursor solution.

[0153] b. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain zinc indium sulfide nanosheet photocatalyst.

[0154] c. By attaching Figure 3 4 It can be seen that the photocatalytic seawater decomposition and hydrogenation rate of the ZIS prepared in this comparative example is 0.52mmol g -1 h -1 The photocatalytic hydrogen release rate of pure water is 0.77 mmol g -1 h -1 .

[0155] Comparative Example 2:

[0156] The first step is to prepare zinc indium sulfide nanosheet photocatalyst: the preparation method is the same as that of comparative example 1;

[0157] The second step is the preparation of ZnInS-Pt single-atom-level heterostructure composite materials:

[0158] a. The obtained 50 mg zinc indium sulfide nanosheet photocatalyst was uniformly dispersed in 80 mL methanol solution by ultrasonic stirring;

[0159] b. The mass ratio of platinum single atom to zinc indium sulfide is 0.75% and the hexahydrate chloroplatinic acid is uniformly ultrasonically dispersed in 20 mL of methanol solution, and slowly added dropwise to the zinc indium sulfide methanol solution in a, and argon gas is introduced to remove impurities, and the mixture is slowly stirred for 48 hours in the dark. The obtained sample is collected by centrifugation, and repeatedly washed with ethanol and water for 4 times, and dried at room temperature in a nitrogen flow for 8 hours to obtain a zinc indium sulfide-platinum single atom (ZIS-Pt SA) hierarchical heterostructure composite material.

[0160] c. By attaching Figure 3 4 It can be seen that the photocatalytic seawater decomposition and hydrogenation rate of the ZIS-Pt SA prepared in this comparative example is 10.44mmol g -1 h -1 The photocatalytic hydrogen release rate of pure water is 17.87 mmol g -1 h -1 .

[0161] Comparative Example 3:

[0162] The first step is to prepare zinc indium sulfide nanosheet photocatalyst: the preparation method is the same as that of comparative example 1;

[0163] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0164] a. 8.466 g of cobalt oxide was evenly dispersed in 50 mL of pure water and stirred vigorously for 10 minutes to obtain a cobalt oxide solution;

[0165] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0166] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0167] d. By attaching Figure 7 It can be seen that the CoO prepared in this comparative example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan.X @ZIS-2.0-pure water photocatalytic hydrogen decomposition rate of pure water is 3.57mmol g -1 h -1 The photocatalytic hydrogen release rate of seawater was 1.12 mmol g -1 h -1 .

[0168] Comparative Example 4:

[0169] The first step is to prepare zinc indium sulfide nanosheet photocatalyst: the preparation method is the same as that of comparative example 1;

[0170] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0171] a. 8.466 g of cobalt oxide was uniformly dispersed in 50 mL of ethanol and stirred vigorously for 10 minutes to obtain a cobalt oxide solution;

[0172] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0173] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0174] d. By attaching Figure 7 It can be seen that the CoO prepared in this comparative example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X The photocatalytic hydrogen decomposition rate of @ZIS-2.0-ethanol in pure water was 5.98 mmol g -1 h -1 The photocatalytic hydrogen decomposition rate of seawater was 3.55 mmol g -1 h -1 .

[0175] Comparative Example 5:

[0176] The first step is to prepare zinc indium sulfide nanosheet photocatalyst: the preparation method is the same as that of comparative example 1;

[0177] Step 2: Preparation of cobalt oxide @ zinc indium sulfide heterostructure composite:

[0178] a. 8.466 g of cobalt oxide was evenly dispersed in 50 mL of glycerol and stirred vigorously for 10 minutes to obtain a cobalt oxide solution;

[0179] b. 272 ​​mg of zinc chloride and 586 mg of indium chloride tetrahydrate were added to the above solution a and dispersed evenly to obtain a reaction precursor solution containing no sulfur source, and stirred for 30 minutes to make it evenly dispersed, and finally 450 mg of thioacetamide was added and dispersed evenly to obtain a reaction precursor solution.

[0180] c. Place the reaction precursor solution in a high temperature reactor at 180°C for 12 hours. After the reaction is completed, cool it naturally to room temperature, and wash it repeatedly by centrifugation with ethanol for 6 times. Collect the obtained product and vacuum dry it at room temperature for 8 hours to obtain a cobalt oxide @ zinc indium sulfide heterostructure composite.

[0181] d. By attaching Figure 7 It can be seen that the CoO prepared in this comparative example is detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X The photocatalytic hydrogen release rate of pure water by @ZIS-2.0-propylene glycol is 12.55 mmol g -1 h -1 The photocatalytic hydrogen decomposition rate of seawater was 6.89 mmol g -1 h -1 .

[0182] In summary, the ZIS, ZIS-Pt SA, CoO prepared in the comparative example were detected by the CEL-PAEM-D8Pro online photocatalytic system of Zhongjiao Jinyuan. X @ZIS-2.0-pure water, CoO X @ZIS-2.0-Ethanol, CoO X The photocatalytic hydrogen evolution rate of @ZIS-2.0-propylene glycol sample is significantly lower than that of the method described in the present invention.

[0183] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

[0184] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.

Claims

1. A method for preparing a heterostructure photocatalyst of a zinc indium sulfide and hollow dodecahedral cobalt oxide inner cage complex anchoring a single platinum atom, characterized in that: The photocatalyst is a hierarchical heterogeneous structure photocatalyst composed of two-dimensional zinc indium sulfide nanosheets rich in sulfur vacancies, which are chemically coated on the outside of a regular dodecahedral cobalt oxide hollow cage by a hydrothermal method, and a single platinum atom is chemically reduced and anchored on the surface of the composite by sulfur vacancies; the mass ratio of the cobalt oxide to the zinc indium sulfide is 0.1-3.0%; the mass ratio of the single platinum atom to the composite of the zinc indium sulfide-coated cobalt oxide is 0.1-1.0%; the preparation method of the heterogeneous structure photocatalyst comprises the following steps: S1, preparing cobalt oxide by air atmosphere heat treatment method: a. Dissolve dimethylimidazole and cobalt nitrate hexahydrate in methanol solution respectively, and quickly pour the evenly mixed dimethylimidazole methanol solution into the cobalt nitrate hexahydrate methanol solution; vigorously stir the obtained purple solution, and let it stand at room temperature for aging; collect the obtained purple precipitate by high-speed centrifugation, then wash it with ethanol and dry it in vacuum at room temperature to obtain the zeolite imidazole ester cobalt metal framework material ZIF-67; b. Grind the dried ZIF-67, place it in a covered porcelain boat, place the porcelain boat in a tubular furnace quartz tube for heat treatment in an air atmosphere, and obtain cobalt oxide, characterized in that the cobalt oxide CoO X The value of X is 1.0~2.0; S2, preparing a sulfur vacancy-rich zinc indium sulfide reaction precursor solution, and chemically anchoring the sulfur vacancy-rich zinc indium sulfide nanosheets on the outer surface of the hollow dodecahedral cobalt oxide hollow cage by a hydrothermal method to construct a cobalt oxide@zinc indium sulfide heterostructure composite; S3, preparing a reaction precursor solution containing Pt, anchoring single platinum atoms on the sulfur vacancies on the surface of the cobalt oxide@zinc indium sulfide complex by dark chemical reduction, and constructing a cobalt oxide@zinc indium sulfide-platinum single-atom-level heterostructure photocatalyst; The specific steps of S3 are: a. uniformly dissolving the obtained cobalt oxide@zinc indium sulfide heterostructure complex in a methanol solution; b. Disperse chloroplatinic acid hexahydrate evenly in a methanol solution, and add dropwise to the cobalt oxide @ zinc indium sulfide methanol solution in a, and introduce argon gas to remove impurities. Stir slowly for 48 hours in the dark and away from light. Collect the obtained sample by centrifugation, wash it with ethanol several times, and dry it at room temperature in a nitrogen flow for 8 hours.

2. The method for preparing a heterostructured photocatalyst according to claim 1, characterized in that: In step a, the mass ratio of dimethylimidazole to cobalt nitrate hexahydrate is 0.5-2.0; the volume of the methanol solution is 50 mL-150 mL; the temperature is increased to 300-400 ° C at a heating rate of 1-5 ° C / min, and the temperature is kept constant for 1 min-60 min, and then naturally cooled to room temperature.

3. The method for preparing a heterostructured photocatalyst according to claim 1, characterized in that The specific steps of S2 are: a. Add cobalt oxide to ethanol, ethylene glycol, glycerol or deionized water and disperse evenly to obtain a cobalt oxide solution; b. adding the zinc source and the indium source to the cobalt oxide solution obtained in step a above and dispersing them uniformly to obtain a reaction precursor solution without a sulfur source, stirring and dispersing them uniformly, and finally adding the sulfur source and dispersing them uniformly to obtain a reaction precursor solution; c. placing the reaction precursor solution in a high temperature reactor for high temperature reaction to obtain a cobalt oxide@zinc indium sulfide heterostructure composite.

4. The method for preparing a heterostructured photocatalyst according to claim 3, characterized in that: In step b, the zinc source is one of zinc chloride, zinc acetate, zinc sulfate, and zinc nitrate; the indium source is indium chloride; the sulfur source is one of thiourea, thioacetamide, sodium sulfide, and sulfur powder; in step b, the atomic ratio of the sulfur source to the zinc source in the precursor solution is S / Zn=4~12.

5. A heterostructure photocatalyst prepared according to the method described in any one of claims 1 to 4.

6. The use of the heterostructure photocatalyst according to claim 5, characterized in that: Heterostructure photocatalysts with complex-anchored platinum single atoms are used for universal hydrogen evolution by photocatalytic splitting of natural seawater or pure water.